"Bedtime is when bad stuff happens": Sleep problems in foster care alumni. (December 2018) - Fusco, Rachel A.; Kulkarni, Shanti J.
Abstract: There is substantial evidence documenting the importance of sleep for positive health and mental health. However, many young adults struggle with getting the sufficient quantity and quality of sleep each night. Individuals who have a history of adverse experiences may be at greater risk for sleep problems. While most studies of sleep and trauma have explored issues such as participating in combat, natural disasters, and child maltreatment, few have focused on the impact of being in foster care. Youth in care have not only the negative effects of abuse and neglect but the challenges of housing instability and adjustment to new caregivers and settings. The current study aimed to learn more about sleep in young adults who have spent time in foster care. Using qualitative data gathered from interviews with 24 foster care alumni, this study examined sleep before entering care, while youth lived in care, and after leaving care and establishing their independence as adults. Three areas were examined across time periods: 1) experience/context of sleep problems; 2) symptoms/behaviors related to sleep problems; and 3) coping strategies for poor sleep and its consequences. Youths' problems with sleep appeared to have greatly impacted their lives and had negative effects upon their relationships, employment, school, and even their foster care placement experiences. Recommendations are made for education about the relationship between trauma and sleep and for interventions that specifically target sleep, such as Cognitive Behavioral Therapy for Insomnia. Highlights: Foster care alumni demonstrate significant problems with insomnia. Insomnia negatively affects their relationships, employment, and educational experiences. Youth report experiences with early abuse and neglect that impacted their sleep patterns. Youth use alcohol and illicit drugs, especially marijuana to help them sleep.